2015
DOI: 10.1007/s40596-014-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction in Greek Medical Students: an Online Survey

Abstract: This is the first IA prevalence study in a European medical school. Early-detection systems and other ways to help students with pathological behaviors should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 9 publications
5
40
2
5
Order By: Relevance
“…Interestingly, the prevalence of possible IA in our study was found to be higher than those of IA observed by similar studies in Chile (11.5%) [14], Iran (10.8%) [15], and Greece (5.6%) [16]. In contrast, a study in Nepal reported almost twice the prevalence of possible IA in Thailand (44.6%) [13].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the prevalence of possible IA in our study was found to be higher than those of IA observed by similar studies in Chile (11.5%) [14], Iran (10.8%) [15], and Greece (5.6%) [16]. In contrast, a study in Nepal reported almost twice the prevalence of possible IA in Thailand (44.6%) [13].…”
Section: Discussioncontrasting
confidence: 83%
“…Nevertheless, losing control of its use can result in negative consequences, such as difficulty completing assignments, sleep deprivation, and poor academic performance [4,13]. Indeed, recent surveys from various countries have reported the prevalence of IA in medical students to be ranging from 5.5–44.6% [13–16]. The affected group reported more emotional symptoms [14] and also appeared to have poorer academic performance as well as lower quality of life in the domain of physical, psychological, and social relation compared to non-affected group.…”
Section: Introductionmentioning
confidence: 99%
“…This finding corresponds with studies among students in Greece, India, Iran and Mexico (cf. Khadzaei et al, 2017;Capetillo-Ventura & Juárez-Treviño, 2015;Kawa & Shafi, 2015;Tsimtsiou et al, 2015;Kalaitzaki & Birtchnell, 2014;Salehi et al, 2014). The present study flagged a relatively high prevalence of two constructs of PIU, namely 'escape from problems' and 'loss of control'.…”
Section: Discussionmentioning
confidence: 48%
“…For the first time, IA disorder was defined as a behavioral addiction by Goldberg which was taken from drug dependency (2). Today, everyone is at risk of IA and youth and university students are at high risk of over-use of the Internet (9).…”
Section: Introductionmentioning
confidence: 99%
“…Medical students have more specific features because they have to study for long hours (9). Given that medical students are at greater risk of IA, which has large effects on mental health of students, this study was performed to evaluate Internet addiction and mental health among medical sciences collegians in southeast of Iran.…”
Section: Introductionmentioning
confidence: 99%